Análisis de la información emitida por los periodistas y medios de comunicación en situaciones de riesgo ante un desastre natural en la ciudad de Loja en el periodo abril-octubre del 2016 - Sánchez Martínez, Hever (2018)
This research work arises from the academic need to know if the journalists and media of the city of Loja are trained in matters of risk situations, to develop journalism in scenarios and crisis circumstances. With this, it was proposed as a general objective: Investigate the media and journalists of the city of Loja are trained to exercise communication in situations of risk from natural disasters in the period April - October 2016, through which the public was informed the Importance that media and journalists should be able to cope with communication in situations of natural disasters, since they have the social duty to educate citizens to avoid wrong actions before, during and after a natural disaster The anthropic. They are the ones who emit responsibly contrasted and timely information. In order to obtain direct information, observation sheets were applied to the mass media in which information about natural disasters was issued, surveys of the city of Loja, and to get to know another point of view, interviews were conducted with specialists in the field of communication in situations of risk